Cybersex behavior and related factors among adolescents in Indonesia - Budiarti, Astrida; Varwani, Mey Lita Eka; Hastuti, Puji; Fatimawati, Iis (Intelektual Pustaka Media Utama, 2024)
Cybersex behavior can lead to potential harm and addiction among adolescents. The aim of this study was to analyze factors that influence cybersex behavior among adolescents. The design used in this study was a cross-sectional. Data was collected from students at senior high school from March to June 2022 using simple random sampling. Total sample was 140 students. The questionnaire were parental sexual communication questionnaires, family monitoring questionnaires, peer interaction questionnaires, internet addiction test (IAT), internet sex screening test. Data was analyzed using Spearman's Rho test. The results showed that parental sexual communication was in the low category (55.7%), family monitoring was in the low category (39.3%), most of the adolescent’s peer interaction was at a moderate level (88.6%), the use of social media was moderate (85%), cybersex behavior was at risk was 97.1%. The results show that there was a relationship between parental sexual communication and cybersex behavior (p=0.002); peer interaction and cybersex behavior (p=0.002), social media and cybersex behavior (p=0.000); family monitoring and cybersex behavior (ρ=0.000) among adolescents. Parental monitoring and communication, social media use education and look for positive peer are important factors to prevent cybersex behavior among adolescents.